Identification of Graduate Research Students’ Resource Needs in a Malaysian Public University - Ismail, Affero (2008)
The desire to pursue higher education is constantly increasing. The government and the institutions of higher learning are striving to attract more students, especially at the graduate level by making every effort to provide quality education. Some scholars proposed that the strategic success of a service organization depends on its ability to consistently meet or exceed customer service expectations. Students need information and support to cope in balancing the demands of the different environments. One of the major problems facing by the higher education nowadays is attrition and completion rates. To sustain a high completion rates, one of the most challenges role of the supervisor is to ensure effective facilitate and responsible to assist the students in their research. In most existing research literature, study on information and services and supervisory system were done separately. Moreover, most of the studies about supervisory system were done by researchers from other countries. However this study took a further step by assembling these needs together in one single research. Therefore this study was conducted in order to explore the students’ needs in both elements so that it will bring to a significant effect of either to the institutional or the students. The main objective of this research is to identify the students’ resource needs in terms of information and services and supervisory system. Questionnaires were sent to 341 graduate students in a public university determined by purposive sampling. They were Master or PhD students with thesis program. 184 (53.96%) of them were returned and usable. This study found that administrative functions, such as information on service and support in terms of bursaries and loans, and student fees may need to be improved. Meanwhile, the information about student support and welfare services also states the lowest mean among these which are 2.00. The lowest mean was International Office (IO) with a mean of 1.79. Only 44% of the respondents found access to computers very accessible, while 2.2% of the respondents indicated that the use of computer facilities did not apply to them. The same general trend applies to the internet access. Highest rank of students’ perception was the treatment from lecturer/tutor with a mean of 3.53. The lowest falls to parking area facilities and the cafeteria with mean of 2.86. The overall rank order of the services’ dimension shows that the poorest services fall to responsiveness with mean of 3.09 for science based faculty and 3.20 for social science based faculty. Empathy falls at the first rank of services’ dimension with mean of 3.30 for science based faculty and 3.51 for social science based faculty. The majority of respondents found that the supervisory aspects generally very accessible with a mean of 2.43. They also agreed that it was very accessible to contact a supervisor with a mean of 3.49. However, selection of supervisor and information on potential supervisor were perceived as moderately accessible. Respondents perceived that time management is very important to them with the highest mean of 4.31. Supervisory contributions in this research were categorized into five which are Managerial, Research, Academic, Language and Interpersonal Input. Respondents perceived that Managerial Input was at the highest priority. It is followed by Research Input with a mean of 4.26. Academic and Interpersonal Input was rating at the third and fourth rank with mean of 4.22 and 4.21. Language inputs fall at the last rank. The learning that takes place during graduate studies is a maturing, must be enhanced with timely and appropriate support. University should provide information and support to graduate students without sacrificing the coherence and generic input needed in any academic program. Further research should be expanded to investigate the students’ needs in more depth as it may have a significant influence on the enhancement of an effective resource.